2022
DOI: 10.1088/1748-9326/ac74d4
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics and the human-wildlife interface in Asia: land use change as a driver of zoonotic viral outbreaks

Abstract: Pandemics have occurred with increasing frequency over the past century as global travel enables rapid cross-continental transmission of viral zoonoses such as coronaviruses and influenzas. Yet the prevalence of global pandemics is also attributable to an increase in the number of these infectious diseases originating in wildlife or domesticated animals in Asia that jump to human hosts. Through a review of scholarly literature, this article argues that three interrelated land use phenomena—biodiversity loss, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Many zoonoses originate from or have as reservoirs non-human primates ( 30 , 149 ). Asia has been the origin of several suspected zoonotic transmission events over the past decades (e.g., previous SARS outbreaks in the 2000s, Nipah virus in 1998, and H5N1 avian influenza virus in the 2000s); underscoring the critical role of the region in the transmission dynamics and the emergence of zoonotic diseases ( 150 ). Surveillance of wildlife hosts and potential reservoirs is a crucial initial step to mitigate the risk of future pandemics ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many zoonoses originate from or have as reservoirs non-human primates ( 30 , 149 ). Asia has been the origin of several suspected zoonotic transmission events over the past decades (e.g., previous SARS outbreaks in the 2000s, Nipah virus in 1998, and H5N1 avian influenza virus in the 2000s); underscoring the critical role of the region in the transmission dynamics and the emergence of zoonotic diseases ( 150 ). Surveillance of wildlife hosts and potential reservoirs is a crucial initial step to mitigate the risk of future pandemics ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…It represents one of the most important drivers in the (re-)emergence of viral zoonoses [ 30 ]. Since deforestation, urbanisation, agriculture and livestock farming have large-scale impacts on the natural landscape, a domino effect is observed in pathogen and host species abundance, exposure rates as well as pathogen coevolution [ 31 , 32 ]. A study conducted by García-Peña et al [ 33 ] found that in areas with high rodent species diversity, the expansion of croplands into pastures and forests increased the risk of zoonotic disease emergence through the circulation of several different types of pathogens such as hantaviruses.…”
Section: Human Impactful Drivers In the (Re-)emergence Of Viral Zoonosesmentioning
confidence: 99%
“…The emergence and reemergence of zoonotic diseases can be attributed to various factors. Some of those factors are described as follows:  Deforestation and animals' habitat destruction for the purpose of expanding agriculture, logging or urbanization has increased the contact between humans, domestic animals, and wildlife, thus, facilitating disease transmission (Goldstein et al 2022).…”
Section: Factor Contributing To the Emergence And Reemergence Of Zoon...mentioning
confidence: 99%